Camptothecin Regulates Microglia Polarization and Exerts Neuroprotective Effects via Activating AKT/Nrf2/HO-1 and Inhibiting NF-κB Pathways In Vivo and In Vitro - He, Dewei; Fu, Shoupeng; Zhou, Ang; Su, Yingchun; Gao, Xiyu; Zhang, Yufei; Huang, Bingxu; Du, Jian; Liu, Dianfeng (Frontiers in Immunology, 2021)
Microglia, the main immune cells in the brain participate in the innate immune response in the central nervous system (CNS). Studies have shown that microglia can be polarized into pro-inflammatory M1 and anti-inflammatory M2 phenotypes. Accumulated evidences suggest that over-activated M1 microglia release pro-inflammatory mediators that damage neurons and lead to Parkinson's disease (PD). In contrast, M2 microglia release neuroprotective factors and exert the effects of neuroprotection. Camptothecin (CPT), an extract of the plant Camptotheca acuminate, has been reported to have anti-inflammation and antitumor effects. However the effect of CPT on microglia polarization and microglia-mediated inflammation responses has not been reported. In our study we found that CPT improved motor performance of mice and reduced the loss of neurons in the substantia nigra (SN) of midbrain in LPS-injected mice. In the mechanism study, we found that CPT inhibited M1 polarization of microglia and promotes M2 polarization via the AKT/Nrf2/HO-1 and NF-κB signals. Furthermore, CPT protected the neuroblastoma cell line SH-SY5Y and dopaminergic neuron cell line MN9D from damage mediated by microglia activation. In conclusion, our results demonstrate that CPT regulates the microglia polarization phenotype via activating AKT/Nrf2/HO-1 and inhibiting NF-κB pathways, inhibits neuro-inflammatory responses and exerts neuroprotective effects in vivo and in vitro.